Recent Advances in Brachytherapy Using Radioactive Nanoparticles: An Alternative to Seed-Based Brachytherapy - Seniwal, Baljeet; Thipe, Velaphi C.; Singh, Sukhvir; Fonseca, Telma C. F.; Freitas de Freitas, Lucas (Frontiers in Oncology, 2021)
Interstitial brachytherapy (BT) is generally used for the treatment of well confined solid tumors. One example of this is treatment of the prostate tumors by permanent placement of radioactive seeds within the prostate gland, where low doses of radiation are delivered for several months. However, successful implementation of this technique is hampered due to several post treatment adverse effects or symptoms and operational and logistical complications associated to it. Recently, with the advancements in nanotechnology, radioactive nanoparticles (radio-NPs) functionalized with tumor specific biomolecules, injected intratumorally, has been reported as an alternative to seed based BT. Successful treatment of solid tumors using radio-NPs has been reported in several preclinical studies, on both mice and canine models. In this article we review the recent advancements in the synthesis and use of radio-NPs as a substitute to seed based BT. Here we discuss the limitations of current seed based BT and advantages of radio-NPs for brachytherapy applications. Recent progress on the types of radio-NPs, their features, synthesis methods and delivery techniques are discussed. The last part of the review focuses on the currently used dosimetry protocols and studies on the dosimetry of nanobrachytherapy applications using radio-NPs. The current challenges and future research directions on the role of radio-NPs in brachytherapy treatments are​ also discussed.